Detection and isolation of chikungunya virus from field collected Aedes albopictus skuse in selected sites, Peninsular Malaysia - Rozilawati H.,; Mohd Masri S,; Zairi J.,; Yahaya M.A.,; Nazni W.A.,; Lee, H.L. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Chikungunya fever, an Aedes borne viral disease, is becoming a serious public health concern today since the first reported outbreak in Port Klang in 1998/99. Recently, more outbreaks were reported in Malaysia. Entomological investigations were conducted in Chikungunya virus cases localities in Peninsular Malaysia which cover Johor, Negeri Sembilan, Melaka, Perak, Pahang and Selangor state in order to identify the vector responsible for transmitting the Chikungunya virus. The adult mosquitoes were collected using modified aspirator and sweep net methods, whereas water holding containers were inspected for larvae. Reverse transcriptase polymerase chain reaction (RT-PCR) were used as the detection of the virus. Positive samples were inoculated on the cell to isolate the virus. The most common species collected at the localities was Aedes albopictus followed by Culex quinquefasciatus, Aedes aegypti and Armigeres sp. Five pools (n=78) of female, adult Aedes albopictus collected from Tangkak, Johor were positive for the Chikungunya virus as detected by reverse transcription-polymerase chain reaction. Three isolates were obtained and grouped with Central/East African genotype. The presence of Chikungunya virus in wild Aedes albopictus indicated that this mosquito is the most likely vector responsible for the transmission of virus to humans in Johor during the outbreak.